Mitochondrial transplantation combined with coenzyme Q10 induces cardioprotection and mitochondrial improvement in aged male rats with reperfusion injury - Soleyman Bafadam; Behnaz Mokhtari; Manoucheher Seyedi Vafaee; Zohreh Zavvari Oscuyi; Samira Nemati; Reza Badalzadeh (Experimental Physiology)
Abstract Ischaemic heart diseases (IHD) are among the major causes of mortality in the elderly population. Although timely reperfusion is a common treatment for IHD, it causes additional damage to the ischaemic myocardium known as ischaemia–reperfusion (IR) injury. Considering the importance of preventing reperfusion injuries, we aimed to examine the combination effect of mitochondrial transplantation (MT) and coenzyme Q10 (CoQ10) in myocardial IR injury of aged male rats. Seventy‐two aged male Wistar rats were randomly divided into six groups: Sham, IR, CoQ10, MT, combination therapy (MT + CoQ10) and vehicle. Myocardial IR injury was established by occlusion of the left anterior descending coronary artery followed by reopening. Young male Wistar rats were used as mitochondria donors. Isolated mitochondria were injected intraventricularly (500 µL of a respiration buffer containing 6 × 106 ± 5 × 105 mitochondria/mL) in MT‐receiving groups at the onset of reperfusion. CoQ10 (10 mg/kg/day) was injected intraperitoneally for 2 weeks before IR induction. Twenty‐four hours after reperfusion, haemodynamic parameters, myocardial infarct size (IS), lactate dehydrogenase (LDH) release and cardiac mitochondrial function (mitochondrial reactive oxygen species (ROS) generation and membrane potential) were measured. The combination of MT and CoQ10 improved haemodynamic index changes and reduced IS and LDH release (P < 0.05). It also decreased mitochondrial ROS generation and increased membrane potential (P < 0.05). CoQ10 also showed a significant cardioprotective effect. Combination therapy displayed greater cardioprotective effects than single treatments. This study revealed that MT and CoQ10 combination treatment can be considered as a promising cardioprotective strategy to reduce myocardial IR injury in ageing, in part by restoring mitochondrial function.